Oxidative Stress and Inflammation Differentially Elevated in Objective Versus Habitual Subjective Reduced Sleep Duration in Obstructive Sleep Apnea - DeMartino, Theresanne (Sleep, 2016)
STUDY OBJECTIVES: Data have demonstrated adverse health effects of sleep deprivation. We postulate that oxidative stress and systemic inflammation biomarkers will be elevated in relation to short-term and long-term sleep duration reduction. METHODS: We analyzed data from the baseline examination of a randomized controlled trial involving participants with moderate to severe obstructive sleep apnea (OSA). Baseline polysomnography provided the total sleep time (PSG-TST, primary predictor); self-reported habitual sleep duration (SR-HSD) data was collected. Morning measures of oxidative stress and systemic inflammation included: myeloperoxidase (MPO, pmol/L), oxidized low-density lipoprotein (ox-LDL, U/L), F2-isoprostane (ng/mg), paraoxonase 1 (PON1, nmol·min(−1)·mL(−1)), and aryl esterase (μmol·min(−1)·mL(−1)). Linear models adjusted for age, sex, race, body mass index (BMI), cardiovascular disease (CVD), smoking, statin/anti-inflammatory medications, and apnea-hypopnea index were utilized (beta estimates and 95% confidence intervals). RESULTS: One hundred forty-seven participants comprised the final analytic sample; they were overall middle-aged (51.0 ± 11.7 y), obese (BMI = 37.3 ± 8.1 kg/m(2)), and 17% had CVD. Multivariable models demonstrated a significant inverse association of PSG-TST and MPO (β [95% CI] = −20.28 [−37.48, −3.08], P = 0.021), i.e., 20.3 pmol/L MPO reduction per hour increase PSG-TST. Alternatively, a significant inverse association with ox-LDL and SR-HSD was observed (β [95% CI] = 0.98 [0.96, 0.99], P = 0.027), i.e., 2% ox-LDL reduction per hour increase SR-HSD. CONCLUSIONS: Even after consideration of obesity and OSA severity, inverse significant findings were observed such that reduced PSG-TST was associated with elevated MPO levels and SR-HSD with ox-LDL, suggesting differential up-regulation of oxidative stress and pathways of inflammation in acute versus chronic sleep curtailment. CLINICAL TRIAL REGISTRATION: NIH clinical trials registry number NCT00607893. CITATION: DeMartino T, Ghoul RE, Wang L, Bena J, Hazen SL, Tracy R, Patel SR, Ackley D, Mehra R. Oxidative stress and inflammation differentially elevated in objective versus habitual subjective reduced sleep duration in obstructive sleep apnea. SLEEP 2016;39(7):1361–1369.